Between Dark & Light The Light Art of Ruth McDermott & Ben Baxter - McDermott, Ruth (2022)
Over the past two decades, a quiet revolution has taken place in the world of light art and design with the introduction of LED technology. Sydney-based artists Ruth McDermott and Ben Baxter have been on the vanguard of this movement, creating innovative and award-winning installation artworks utilizing the capabilities of this new technology. A frequent highlight of the Vivid Sydney light art festival, their work has become known for creating site-specific narratives exploring the landscapes and histories of Sydney and its surrounds. This book surveys twelve years of their practice (2009-2021), as their work evolved in tandem with the technology, with a special focus on the technical aspects of creating, mounting, and displaying large-scale installations. Along with an essay on the history of light art, commentary from collaborators, and over 100 photographs documenting the conceptual life span of eighteen artworks, this book features the authors reflections on the unique relationship of artistic collaboration, and how this relationship has enhanced their practice and journey as artists.